POPULATION-BASED ASSESSMENT OF THE RECTAL CANCER STAGE STRUCTURE AND INCIDENCE AFTER IMPLEMENTATION OF THE NATIONAL PROJECT “HEALTH” AND ALL-NATIONAL DISPENSARIZATION IN THE ARKHANGELSK REGION, RUSSIA (THE RESULTS OF THE PRELIMINARY STUDY) - D. M. Dubovichenko; M. Y. Valkov; A. A. Karpunov; A. Yu. Pankrat'eva (Исследования и практика в медицине)
Objective. Assessment of the rectal cancer (RC) incidence and stage structure trends in the Arkhangelsk region (AR), Russia before and after implementation of national programs for health system reforming based on population data of the Arkhangelsk Regional Cancer Registry (ARCR) over the period 2000–2015.Materials and methods. Anonymized data on all cases of RC (C19.0‑C21.0) in the AR in 2000–2015 were extracted from the database of the ARCR. Over the study period, 3721 cases of the RC were selected. Age-standardized (ASR) RC incidence rate was calculated. Population number and its age distribution were taken from the Regional Bureau of Statistics, Arkhangelskstat. Time trends were analyzed using segmented regression.Results. Over the period, an incidence (ASR) of RC in AR increased from 11.5 to 14.2 per 100000. The incidence rates in the male population were higher than in women: 20.3 vs 12.6 in 2015. The growing trend of male incidence was stable. The ASR of RC incidence in female increased significantly by 4.6% per year in 2011–2015. RC ASRs for both urban and rural populations were growing, 12.3 and 20.4 per 100000 in 2015, respectively. StagesI, II, III and IV were established in 14%, 50%, 9% and 21% of cases, however, the stage I in urban residents was detected 4% more often. The proportion of stage I non-significantly varied from 10.6% to 13.3% in 2000–2015. After the introduction of the National Project “Health”, the proportion of the stage IV non-significantly decreased by 5.4% per year, same after the introduction of the All-national Dispensarization it non-significantly increased by 5.4% per year.Conclusion. Implementation of national programs for health system reforming didn’t provide significant improvement in earlier detection of RC. Introduction of national screening programs is necessary. A higher incidence rates among males and rural population require detailed analysis.